Multidisciplinary treatment approach for correction of facialasymmetry: 3 cases - ACAR, ZEYNEP AHÜ; ACAR, YASEMİN BAHAR; YILDIRIM, GAMZE (My University, 2019)
AIM: Ideal treatment planning for the correction of severe skeletal malocclusion is orthodontics combined with orthognathic surgery. This poster aims to present multidisciplinary treatment of 3 cases with Class III malocclusion and mandibular deviation. MATERIAL-METHOD: Three female patients with the chief complaints of mandibular prominence and facial asymmetry were admitted to treatment in our clinic. Case 1, clinically had asymmetrical face, adequate lip closure, normal smile-line, concave profile; dental Class III relationship and posterior openbite on the right. Lateral cephalometric evaluation showed SNA:75°, SNB:79°, ANB:-4°, I-SN:104 °, IMPA:87 °, Witts:- 4.5mm and low angle vertical growth pattern. Postero-anterior cephalometric measurements revealed 1.0mm shifting of menton to left and 3° counterclockwise occlusal cant. Case 2 had asymmetric face, insufficient lip closure, low smile-line, convex profile; dental Class III relationship and circular openbite. Cephalometric values showed SNA:79°, SNB:77°, ANB:2°, I-SN:106°, IMPA:78°, Witts:-13mm and high angle vertical growth pattern. Menton point was shifted 10.6 mm to left and the occlusal cant was 2° counterclockwise. Case 3 had asymmetrical face, adequate lip closure, normal smile-line, flat profile; dental Class III relationship, crossbite on the left posterior and edge-to-edge bite at the anterior region. CephalometricvaluesshowedSNA:83°,SNB:81°,ANB:2°,I-SN:105°,IMPA:86°,Witts:-5.5mmandhigh angleverticalpattern. Menton pointwas 6.4 mm to left and occlusalcantwas 3° counterclockwise. Non-extraction orthodontic decompensation treatment was planned and patients underwent orthognatic surgery when model surgery displayed stable occlusion. The total duration of treatment was 25, 20 and 19 months, respectively. CONCLUSIONS: Class I molar and canine relationship, ideal overbite and overjet were achieved with the orthodontic and surgical treatment. Sagittal and transversal jaw relations were improved and facial symmetry was improved. As a result, patients were provided with good function and satisfactory aesthetics.

AMAÇ: Şiddetli iskeletsel maloklüzyona sahip yetişkin hastalarda ideal tedavi planlaması, ortodontik dekompansasyonu takiben uygulanan ortognatik cerrahi ile olmaktadır. Bu bildirinin amacı; iskeletsel Sınıf III maloklüzyon ve mandibuler asimetriye sahip üç bireyin ortodonti ve cerrahi işbirliği ile tedavisini sunmaktır. GEREÇ-YÖNTEM: 3 yetişkin kadın hasta mandibular belirginlik ve yüz asimetrisi şikâyetleriyle kliniğimize başvurmuştur. Vaka 1’in klinik muayenesinde yeterli dudak kapanışı, normal gülme hattı, içbükey yüz profili, mandibülerasimetri iledişselolarak SınıfIII ilişkive sağposterioraçık-kapanışgözlenmiştir. Lateral sefalometrik değerlendirmede SNA:75°, SNB:79°, ANB:-4°, I-SN:104°, IMPA:87°, Witts:– 4.5mm, dikey yönde azalmış açı ve boyutlar izlenmektir. Postero-anterior sefalometrik ölçümlerinde mentonda 1.0 mm sola deviasyon ve saat yönünün tersinde 3° oklüzal kant ölçülmüştür. Vaka 2’nin klinik muayenesinde asimetrik yüz, yetersiz dudak kapanışı, düşük gülme hattı, dışbükey yüz profili ile dişsel olarak Sınıf III ilişki ve çevresel açık-kapanış mevcuttur. Sefalometrik olarak SNA:79° SNB:77° ANB:2°, I-SN:106°, IMPA:78°, Witts:– 13.3mm; dikey yönde artmış açı ve boyutlar;. mentonda 10.6 mm sola deviasyonve saatyönünün tersinde 2° oklüzalkant ölçülmüştür Vaka 3’ün klinik muayenesinde asimetrik yüz, yeterli dudak kapanışı, normal gülme hattı ve düz yüz profili ile dişsel olarak Sınıf III ilişki, sol posteriorda çapraz kapanış ve anteriorda başbaşa kapanış gözlemlenmektedir. Sefalometrik olarak SNA:83°, SNB:81°, ANB:2°, I-SN:105°, IMPA:86°, Witts:– 5.5mm, vertikal yönde artmış açı ve boyutlar; mentonda 6.4 mm sola deviasyon, saat yönünün tersinde 3° oklüzal kant ölçülmüştür. Çekimsiz ortodontik tedavi ile dişsel dekompanzayonu takiben hastalar ortognatik ameliyata alınmışlardır. Toplam tedavi süreleri sırasıyla 25, 20 ve 19 aydır. SONUÇ: Ortodonti ve cerrahi tedavi ile Sınıf I molar ve kanin ilişki, ideal overbite ve overjet elde edilmiş, sagittal ve transversal yönde çene ilişkileri düzeltilmiş, yüz simetrisi iyileştirilmiştir. Hastalara iyi bir fonksiyon ve tatmin edici bir estetik sağlanmıştır.
Yüz asimetrisi düzeltiminde multidisipliner tedavi yaklaşımı: 3 olgu sunumu